Contributions of Accessibility and Visibility Characteristics to Neighborhood Typologies and their Predictions of Physical Activity and Health - van der Westhuizen, Diaan (7th International Space Syntax Symposium, 2009)
In recent years, numerous studies have examined the effects of the built environment on physical activity and health outcomes. While much of this research has focused on discrete environmental measures, such as housing density, land use, or the presence or absence of sidewalks, recent studies have addressed the combined effects of ‘bundles’ of environmental measures. As part of a program of research aimed at understanding neighborhood effects on the physical activity and health of residents in three Detroit MI (USA) neighborhoods, this paper describes the process of creating micro-neighborhood types and their hypothesized affects on local physical activity and health outcomes. In particular, we consider the additive predictive significance of incorporating into our micro-neighborhood types measures of street network characteristics (connectivity and accessibility) and objective measures that capture aspects of design quality (based on visibility measures) along walking paths. Based on the theoretical significance of sets of variables from previous studies, and an analysis of the environmental characteristics of our study neighborhoods, we propose nine 'bundles' of neighborhood characteristics or micro-neighborhood types to be assessed as potential factorsaffecting our outcome variables of physical activity and health. Our intent was to identify a reasonable number (<10) of neighborhood types that shared readily observable differences that could be easily adopted by planners and designers.Patterns of residential density and land use were examined across all study neighborhoods and used to create our basic set of nine types. For the purposes of our data analysis, we further divide our typologies into sub-categories to examine the impact of different types of land uses and their projected multiplying effects as enhancers or deterrents to destination walking. Using aerial photographs and syntax analysis, we consider measures of street network characteristics (connectivity and accessibility), and the role of objective measures that capture aspects of design quality (based on measures of visibility: visual access, visual control and visual interest) along walking paths. Contributions of this study include the identification of critical 'bundles' of physical environmental characteristics that play a role in the creation of neighborhoods that support physical activity. Our current analyses are quite suggestive in postulating the contribution of syntax measures in capturing aspects of the design quality (path characteristics) and ease of reaching destinations (network characteristics) that shape respondents’ perceptions of their environment and contribute to physical activity outcomes. In future analyses we will examine the role of these characteristics in augmenting the predictive power of our neighborhood typologies.
Proceedings of the 7th International Space Syntax Symposium Edited by Daniel Koch, Lars Marcus and Jesper Steen, Stockholm: KTH, 2009.
Keywords: environmental typology; physical activity; health outcomes; space syntax